Prevalence, associated factors, mood and cognitive outcomes of traumatic brain injury in later life: the health in men study (HIMS). (20th February 2015) - Almeida, Osvaldo P.; Hankey, Graeme J.; Yeap, Bu B.; Golledge, Jonathan; Flicker, Leon
Abstract : Background: The incidence of traumatic brain injury (TBI) is rising, as are its neuropsychiatric complications. This study aims to determine (1) the prevalence of TBI, (2) the association between history of past TBI and sociodemographic, lifestyle and clinical factors, and (3) the risk of depression and cognitive impairment in later life associated with exposure to TBI. Methods: Cross‐sectional study of a community‐derived sample of 5486 Australian men aged 70–89 years. Information on TBI was retrieved from the Western Australian Data Linkage System (WADLS) and via self‐report. We used the WADLS and self‐report to ascertain history of past depression, and the Geriatric Depression Scale 15‐items to assess current clinically significant symptoms of depression, defined by score ≥7. We defined cognitive impairment by a mini‐mental state examination score <24 or a WADLS diagnosis of dementia. Results: Nine hundred fifty‐three men had history of TBI (17.4%). Factors associated with TBI included coronary heart disease, stroke, poor self‐perceived physical health and falls. TBI increased the odds ratio of past (odds ratio ( OR ) = 1.55, 95% confidence interval ( CI ) = 1.21, 1.99) and current depression ( OR  = 1.77, 95% CI  = 1.36, 2.32), as well as of cognitive impairment ( OR  = 1.23, 95% CI  = 1.00, 1.51). The population fractions of depression and cognitive impairment attributable to TBI were 6.9% (95% CI  = 3.3%, 10.3%) and 3.4% (95% CI  = 0.0%, 6.9%). Conclusions: History of TBI is common in older men, and is associated with increased risk of depression and cognitive impairment. If this association is truly causal, then the effective reduction of events leading to TBI (e.g., motor vehicle accidents and falls) may also decrease the prevalence of depression and cognitive impairment in later life. Copyright © 2015 John Wiley & Sons, Ltd.